Clopidogrel Plus Aspirin in Patients With Different Types of Single Small Subcortical Infarction - Wang, Guangyao; Yang, Xiaomeng; Jing, Jing; Zhao, Xingquan; Liu, Liping; Wang, Chunxue; Wang, David; Wang, Anxin; Meng, Xia; Wang, Yongjun; Wang, Yilong (Frontiers in Neurology, 2021)
Background We aim to investigate the effects and safety of clopidogrel plus aspirin in patients with different types of single small subcortical infarction (SSSI) in the Clopidogrel in High-risk patients with Acute Non-disabling Cerebrovascular Events trial. Methods SSSI was defined as single DWI lesion of ≤2.0 cm. Patients with SSSI were divided into SSSI+PAD (parent artery disease) and SSSI-PAD, according to the stenosis of the parent artery. The efficacy outcome was stroke recurrence during 90-day follow-up. Cox proportional hazards models or logistic regression models were used to assess the interaction of the treatment effects of clopidogrel plus aspirin versus aspirin alone among patients with and without PAD. Results Among 338 patients with SSSI included in the subanalysis,105 were with PAD and 233 without. The efficacy of clopidogrel plus aspirin compared with aspirin alone on any stroke was consistent between patients with (adjusted hazard ratio [HR] 0.84; 95% confidence interval [CI], 0.25-2.75) and without PAD (adjusted HR 1.03; 95% CI, 0.40-2.68, interaction P=0.83). In patients with SSSI+PAD, the rate of stroke recurrence in those treated with dual antiplatelet therapy and mono antiplatelet therapy was not significantly different (10.9% vs 13.6%, P=0.77). The number of bleeding events was similar between the clopidogrel-aspirin group and aspirin group regardless of SSSI+PAD or SSSI-PAD. Conclusions There was no significant difference in the efficacy of clopidogrel plus aspirin compared with aspirin alone between patients with SSSI+PAD and SSSI-PAD in the CHANCE trial. Studies in other populations and with adequate power are needed to further verify such findings.